STRATEGY FOR INSTILLING BASIC RELIGIOUS HUMANIST VALUES IN EARLY CHILDHOOD AT RA AL-HIDAYAH SUNGGAL - Sit, Masganti; Sumanti, Solihah Titin; Siregar, Indah Sari (JURNAL TARBIYAH, 2023)
The current acceleration of digitalization at least erodes the religious humanist values in children. This study aims to analyze the strategy of instilling basic religious humanist values in early childhood at RA Al-Hidayah Sunggal. This study uses a qualitative approach with the method of case studies (case study), data collection instruments using the method of observation, interviews, study documentation. Furthermore, the data were analyzed using data reduction, data presentation, and drawing conclusions. The results of this study concluded that first, the basic religious humanist values that were instilled in RA Al-Hidayah Sunggal students were the value of freedom, the value of creativity, the value of cooperation, the value of honesty, and the value of self-actualization. Second, the method of instilling basic religious humanist values in early childhood is carried out using four methods, namely the BCM (Playing, Story and Singing) Method, the habituation method, the exemplary method, and the advice method. Third, the media in instilling basic religious humanist values in early childhood, namely using the media of people, games, pictures, story books, animated films, laptops, projectors, music and motion.